Physical Activity in Physical Education Learning on Optimizing Students' Neuromuscular System: A Literature Review - Prima Suci Ibar Wati Ningrum; Sugiharto Sugiharto; Sapto Adi (Jurnal Pendidikan Sains, 2021)
Abstract: This literature review aims to analyze the optimization of physical activity in neuromuscular students. Of the 4 databases (google scholar, ScienceDirect, Hindawi, and PubMed with a span of the last 10 years (2011-2021)) searched using the appropriate keywords. The keywords used to analyze the appropriate article are physical education, physical activity, neuromuscular, neurotransmitters, acetylcholine, dopamine, motoric function, student. Data extraction and analysis using PRISMA flowcharts. The results of an analysis of 30 articles showed that physical education learning has an effect on the optimization of acetylcholine, dopamine optimization, and neuromuscular optimization in performing the speed of extraction. Based on the results of the analysis it can be concluded that physical activity plays an important role in the optimization of the neuromuscular system of students.Abstrak: Literature review ini bertujuan untuk menganalisis optimalisasi aktivitas fisik pada neuromuscular siswa. Dari 4 data base (googlescholar, sciencedirect, hindawi, dan PubMed dengan rentang waktu 10 tahun terakhir (2011-2021)) dicari menggunakan kata kunci yang sesuai. Kata kunci yang digunakan untuk menganalisis artikel yang sesuai adalah physical education, physical activity, neuromuscular, neurotransmitter, asetilkolin, dopamine, motoric function, student. Ekstraksi data dan analisis menggunakan diagram alur PRISMA. Hasil analisis 30 artikel menunjukkan bahwa pembelajaran pendidikan jasmani berpengaruh terhadap optimalisasi asetilkolin, optimalisasi dopamin, dan optimalisasi neuromuscular dalam melakukan kecepatan kotraksi. Berdasarkan hasil analisis dapat disimpulkan bahwa aktivitas fisik sangat berperan penting terhadap optimalisasi sistem neuromuscular siswa.